IMPLEMENTING PROBLEM BASED LEARNING TO INCREASE HIGH SCHOOL STUDENT’S INTEREST IN CRITICAL THINKING SKILLS - VERONIKA FATMA UTAMI, DENIS; JATMIKO, BUDI (Inovasi Pendidikan Fisika, 2018)
Learning conventional cause interest students to learning physics is low. This research aims to describe student?s response in problem based learning. The type of research is pre-experimental design with quantitative descriptive analysis. The subject is 93 students in SMAN 1 Taman divided by three class are X MIA 2, X MIA 4, X MIA 5 that selected on random sampling. The instrument is questionnaire responses form were filled by students after receive learning. The data analyzed by percentage response from amount score each aspect and categorized based on Likert scale. The results show that response students to problem based learning categorized in good with the average 72,6% and could improve the interesting of critical thinking skills.Keywords: Problem Based Learning, Student?s Response, Critical Thinking